2017
DOI: 10.3390/ijms18091871
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Telomere Length in Colorectal Cancers for Improved Molecular Diagnosis

Abstract: All tumors have in common to reactivate a telomere maintenance mechanism to allow for unlimited proliferation. On the other hand, genetic instability found in some tumors can result from the loss of telomeres. Here, we measured telomere length in colorectal cancers (CRCs) using TRF (Telomere Restriction Fragment) analysis. Telomeric DNA content was also quantified as the ratio of total telomeric (TTAGGG) sequences over that of the invariable Alu sequences. In most of the 125 CRCs analyzed, there was a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 53 publications
6
21
1
Order By: Relevance
“…A recent study investigating telomere length in CRC determined that KRAS ‐mutated cells exhibited extensive telomere shortening compared with control cells. In contrast, cells that carried BRAF mutations or were classified as MSI did not exhibit telomere defects (Balc'h et al ., ). Another independent study analyzed telomere length in precursor colorectal lesions and observed that telomere shortening was associated with mitochondrial microsatellite instability in the tumor tissue samples and with KRAS and BRAF mutations in the normal tissues (Park et al ., ).…”
Section: Dna Repair‐defective Phenotypes In Colorectal Cancersmentioning
confidence: 99%
“…A recent study investigating telomere length in CRC determined that KRAS ‐mutated cells exhibited extensive telomere shortening compared with control cells. In contrast, cells that carried BRAF mutations or were classified as MSI did not exhibit telomere defects (Balc'h et al ., ). Another independent study analyzed telomere length in precursor colorectal lesions and observed that telomere shortening was associated with mitochondrial microsatellite instability in the tumor tissue samples and with KRAS and BRAF mutations in the normal tissues (Park et al ., ).…”
Section: Dna Repair‐defective Phenotypes In Colorectal Cancersmentioning
confidence: 99%
“…In the first category with tissue samples, the results varied. Two studies revealed better prognosis in patients with longer telomere length, and only stage IV patients were recruited in these two studies 8,9 ; four studies revealed better prognosis in patients with shorter telomere length or lower TL ratio [10][11][12][13] ; four studies did not show any significant association between tumor length and prognosis 14,15-17 . In the next category with blood samples, two studies presented contradictory results regarding the correlation between telomere length and survival rate 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Balc'h et al measured telomere length from 125 CRC tissue samples 8 . A significant shortening of telomere length in the tumor tissue compared with the normal tissue was observed.…”
Section: Studies Finding Associations Between Telomere Length and Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is also batch effect on TL during DNA preparation. A recent study on reproducibility of TL measurement in different laboratories across the globe suggests high inter-laboratory coefficients of variation (CVs) which were about 10% and 20% for Southern blotting and qPCR, respectively [27].There is also large variation of TL due to ethnicity, making it difficult to analyze TL data in mixed multicultural population studies [28].In some studies, the TL in pathological tissue was compared with that in adjacent healthy tissue (31)(32)(33)(34)(35) to eliminate the impact of other variables or batch effect. However, this may not be ideal because adjacent tissue could also be abnormal if etiological exposure affected a large area or whole organ [34,35].…”
Section: Introductionmentioning
confidence: 99%